Pricing and waiting time decisions in a health care market with private and public provision - Vasco F. Alves (Journal of Applied Economics, 2019)
This paper describes a duopoly market for healthcare where one of the two providers is publicly owned and charges a price of zero, while the other sets a price so as to maximize its profit. Both providers are subject to congestion in the form of an M/M/1 queue, and they serve patient-consumers who have randomly distributed unit costs of time. Consumer demand (as market share) for both providers is obtained and described. The private provider's pricing decision is explored, equilibrium existence is proven, and conditions for uniqueness presented. Comparative statics for demand are presented. Social welfare functions are described and the welfare maximizing condition obtained. More detailed results are then obtained for cases when costs follow uniform and Kumaraswamy distributions. Numerical simulations are then performed for these distributions, employing several parameter values, demonstrating the private provider's pricing decision and its relationship with social welfare.
Keywords: 330; competition; private health care; queueing; Waiting times